Effects of Sex and Age on Quadriceps and Hamstring Strength and Flexibility in High School Basketball Athletes - Takashi Nagai; Nathaniel Bates; April McPherson; Rena Hale; Timothy Hewett; Nathan D. Schilaty (International Journal of Sports Physical Therapy)
# Background